Activity and rational combinations of a novel, engineered chimeric, TRAIL-based ligand in diffuse large B-cell lymphoma - Piechna, Karolina; Żołyniak, Aleksandra; Jabłońska, Ewa; Noyszewska-Kania, Monika; Szydłowski, Maciej; Żerek, Bartłomiej; Kulecka, Maria; Rumieńczyk, Izabela; Mikula, Michał; Juszczyński, Przemysław (Frontiers in Oncology, 2022)
Background: TRAIL (TNF-related apoptosis inducing ligand) exhibits selective proapoptotic activity in multiple tumor types, while sparing normal cells. This selectivity makes TRAIL an attractive therapeutic candidate. However, despite encouraging activity in preclinical models, clinical trials with TRAIL mimetics/death receptor agonists demonstrated insufficient activity, largely due to emerging resistance to these agents. Herein, we investigated the cytotoxic activity of a novel, TRAIL-based chimeric protein AD-O51.4 combining TRAIL and VEGFA-derived peptide sequences, in hematological malignancies. We characterize key molecular mechanisms leading to resistance and propose rational pharmacological combinations sensitizing cells to AD-O51.4. Methods: Sensitivity of DLBCL, classical Hodgkin lymphoma, (cHL), Burkitt lymphoma (BL) and acute myeloid leukemia (AML) to AD-O51.4 was assessed in vitro with MTS assay and apoptosis tests (Annexin V/PI staining). Markers of apoptosis were assessed using immunoblotting, flow cytometry or fluorogenic caspase cleavage assays. Resistant cell lines were obtained by incubation with increasing doses of AD-O51. Transcriptomic analyses were performed by RNA sequencing. Sensitizing effects of selected pathway modulators (BCL2, dynamin and HDAC inhibitors) were assessed using MTS/apoptosis assays. Results: AD-O51.4 exhibited low-nanomolar cytotoxic activity in DLBCL cells, but not in other lymphoid or AML cell lines. AD-O51.4 induced death-receptor (DR) mediated, caspase-dependent apoptosis in sensitive DLBCL cells, but not in primary resistant cells. The presence of DRs and caspase 8 in cancer cells was crucial for AD-O51.4-induced apoptosis. To understand the potential mechanisms of resistance in an unbiased way, we engineered AD-O51.4-resistant cells and evaluated resistance-associated transcriptomic changes. Resistant cells exhibited changes in the expression of multiple genes and pathways associated with apoptosis, endocytosis and HDAC-dependent epigenetic reprogramming, suggesting potential therapeutic strategies of sensitization to AD-O51.4. In subsequent analyses, we demonstrated that HDAC inhibitors, BCL2 inhibitors and endocytosis/dynamin inhibitors sensitized primary resistant DLBCL cells to AD-O51.4 . Conclusions: Taken together, we identified rational pharmacologic strategies sensitizing cells to AD-O51.4, including BCL2, histone deacetylase inhibitors and dynamin modulators. Since AD-O51.4 exhibits favorable pharmacokinetics and an acceptable safety profile, its further clinical development is warranted. Identification of resistance mechanisms in a clinical setting might indicate a personalized pharmacological approach to override the resistance.